FERNANDO MATEOS, S. J., MIGUEL OTEGUI, S. J., e IGNACIO ARRIZABALAGA, S. J. (eds.), Diccionario español de la lengua china. Madrid: Espasa-Calpe, S. A., 1977, pp. xxxviii + 1140 + 179. - -, - (Estudios de Asia y África, 1980)
-